(untitled) - Sadiq, Waqar (Cambridge, 2003)
This book introduces a new industry technology, Business Service Orchestration (BSO). Section I provides detailed overview of business services and their orchestration and describes an in-depth architecture necessary to provide a web of business services, and orchestration of their interactions, including a methodology for modeling the BSO. Section II focuses on technologies necessary to orchestrate business services, ranging from component models to programming languages to various kinds of protocols. Section III reveals a real use case and explains how to apply orchestration to a real-life business process.
Keywords: Business information services,Thông tin dịch vụ kinh doanh,Business,Kinh doanh; Computer network resources,Nguồn tài nguyên mạng máy tính